Arboreal vegetation structure and diversity in the gallery forest of the Xaltatempa river, Puebla, Mexico - Aguilar-Luna, Jesús Mao Estanislao; Loeza-Corte, Juan Manuel; García-Villanueva, Eduardo; Hernández-Fernández, Luis Alejandro (Instituto de Ecología, A.C., 2018)
Gallery forests are plant formations that develop parallel to rivers. They possess a great plant diversity; whose arboreal species are indicative of water quality. Here are described the variables of the arboreal plant life and their relationship with the water quality of the Xaltatempa river, Puebla, Mexico. To do this, six sampling units were established, each 1000 m2, separated by 2 km, where all the trees and shrubs were measured and identified in order to generate information regarding: importance value index (IVI), forestry value index (FVI), Shannon-Weaver heterogeneity index (H'), and Sorensen's similarity index (SSI). Additionally, river water samples were taken to determine its main chemical characteristics. The results indicated a statistical difference between sites (α≤0.05), where the most important species, given its dominance, density, and frequency, was Platanus mexicana (IVI=182.71); it was also the most important for its diameter, height, and cover (FVI=300.00). Specific richness (H'=0.54) was found in only six species: Alnus acuminata, Ligustrum japonicum, Parathesis serrulata, Pinus patula, Platanus mexicana, and Quercus rugosa. With regard to SSI, the paired combination of sites 4 (1586 m asl) and 5 (1536 m asl) matched the following species: Alnus acuminata, Ligustrum japonicum, and Platanus mexicana (SSI=1.00). The structure (fragmented) and diversity (very low) of the arboreal plat life of the gallery forest evidence the changes in its composition, without any negative effects on water quality for its exploitation.